PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK PESAWAT SEDERHANA DI KELAS VIII SMPN 14 MEDAN - Surbakti, Mariana; Manullang, Romauli; Pane, Januari (Jurnal Visi Eksakta, 2021)
The Objective of this research is to know the effect of using Problem Based Learning (PBL) on Learning Outcomes of Students in The Simple Machine In Grade VIII The First Semester SMP Negeri 14 Medan Academic Year 2019/2020. The research method is true Eksperimental . The Population was all students at grade VIII of SMPN 14 Medan Academic Year 2019/2020. The Samples to conduct this research were two classes, class VIIIF as the experiment class and class VIIID as control class, definid by random cluster sampling. The research instrument are learning achievement test and student activity observation sheet. The result that were obtained was: post-test mean value of the experiment class was 58,55 and 50,00 for control class. Deviation standart for two classes was 12,12 and 12,38. From the calculation of t-test one side for α=0,05 and n=60, obtained tcount>ttable where tcount= 1,80 and ttable=2,78. So it can be concluded that there was an effect of using Problem Based Learning (PBL) on Learning Outcomes of Learner in The Simple MachineTopic In Grade VIII The First Semester SMPN 14 Medan Academic Year 2019/2020 with calculation of linear regression were = 22,50 + 0,59X. It can be seen from the increase in student learning out comes by 17%